A teleoperated snake-like robot for minimally invasive radiosurgery of gastrointestinal tumors - Omisore, Olatunji Mumini; Han, ShiPeng; Ren, LingXue; Zhao, ZhiChun; Al-Handarish, Yousef; Igbe, Tobore; Wang, Lei (2018 IEEE International Conference on Autonomous Robot Systems and Competitions (ICARSC), 2018)
Despite the wide acceptability of brachytherapy, precise placement of short-range radiation sources on gastrointestinal tumor is still a problem. Recently, a good number of studies have proposed different flexible robotic models for minimally invasive surgical and radiotherapeutic procedures for such in-body abnormal tissue growth. However, existing robotic designs are hindered by spatial inflexibilities of arm robots controlling the source delivery and inexistence of ideal control models for redundant robots. This study presents a snake-like robot for minimally invasive radiosurgery of gastrointestinal tumors. Efficient kinematic and dynamic models are presented for effective control and teleoperation of the robot. Similarly, a direct model is formulated for mapping workspaces of the master and slave devices, based on their kinematics. Simulations and in-vitro trial were carried out to validate operation of the robot. Analysis of the results obtained show that the snake robot can be fitted for real clinical settings.